Synthesis of calcium phosphate particles via the solution combustion method and investigation of the effects of initial pH and heat treatment temperature on the physical and biological properties of the produced powder - Neda Sami; Sahar Mollazadeh Beidokhti; Jalil Vahdati Khaki (مواد نوین)
Introduction: Hydroxyapatite is a natural mineral found in bone components. Fluoride ions can replace its hydroxyl group to form a wide range of apatites. Fluoroapatite is one of the materials that can release F- ions at a controlled rate. Fluoride ion replacement improves cell proliferation and activation of osteogenic cells to the implant surface. Methods: In this study, calcium phosphate particles were synthesized by combustion synthesis in solutions with different amounts of alkaline agent and at ambient temperature. The synthesized particles were dried to varying pHs after washing and centrifugation in a vacuum environment and at 90℃. After preparing powders, all samples were heat treated at a temperature range of 850 to 1100°C. The physical and biological properties of the samples prepared at different pHs and temperatures were investigated. Findings: The results showed that increasing the solution's pH and heat treat temperature increased the release of fluoride ions. It was also found that increasing the pH in the initial synthesis solution decreased the particle size from about 500 nm at pH=8 to 100 nm at pH=10. This is due to the improvement in the uniformity of the initial synthesis solution. The result of this research can be a substitute for damaged bone tissue. Because it simultaneously contains two phases of hydroxyapatite and fluorapatite, which will lead to the control of the release and absorption of mineral ions. Conclusion: In conclusion, hydroxyfluoroapatite particles produced through combustion synthesis in solution exhibit promising characteristics for bone tissue repair. The synthesized samples retain their fluoroapatite phase after contact with simulated body fluid for three weeks, demonstrating chemical stability. Furthermore, the presence of hydroxyapatite enhances the release of fluorine ions, indicating potential suitability for bioremediation. Therefore, the combination of hydroxyapatite and fluoroapatite phases offers a viable option for effective bone tissue regeneration.